Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Tenofovir Alafenamide Fumarate and Emtricitabine in Bulk and Tablet Dosage Form - Kalamkar, Chaitali S; Bhawar, Sanjay B (Journal of Drug Delivery and Therapeutics, 2019)
New Analytical method was developed for the estimation of Emtricitabine and Tenofovir Alafenamide Fumarate in drug product by liquid chromatography. The chromatographic separation was achieved on Cosmosil C18 column (250mm×4.6ID, 5µm) at ambient temperature. The separation achieved employing a mobile phase consists of Methanol:water(80:20v/v). The flow rate was 0.8ml/ minute and ultra violet detector at 252nm. The average retention time for Emtricitabine and Tenofovir Alafenamide Fumarate found to be 4.277min and 5.293min. The proposed method was validated for selectivity, precision, linearity and accuracy. All validation parameters were within the acceptable range. The assay methods were found to be linear from 10-50µg/ml for Emtricitabine and 15-75µg/ml for Tenofovir Alafenamide Fumarate. Keywords: Emtricitabine and Tenofovir Alafenamide Fumarate, HPLC, Methanol and validation.